Valuing the User Experience in Library Publishing - Betz, Sonya; Hatherill, Jeanette; Stranack, Kevin (Université d'Ottawa | University of Ottawa, 2017)
Libraries are increasingly pushing the boundaries in their roles as content creators and publishers of scholarly journals, monographs, educational resources, and multi-media digital projects. In this rapidly shifting landscape, the tools and platforms we use to create content and make it accessible are critical to our work. However, often little attention is paid to the usability of these tools, less so to the user experience of readers, authors, reviewers, and editors and the role that it plays in the adoption and success of library publishing programs and services. How can improving the user experience of publishing tools contribute positively to advancing the goals of library publishing and open access in the highly competitive commercial world of academic publishing? Why should libraries and developers of publishing platforms care about the user experience of authors, readers, and editors?